Prevalence of medically unexplained symptoms in adults who are high users of health care services: a systematic review and meta-analysis protocol - Ferozkhan Jadhakhan; Oana C Lindner; Amy Blakemore; Elspeth Guthrie (BMJ Open)
Introduction Medically unexplained symptoms (MUS) are common in primary-care and secondary-care settings. Persistent symptoms of MUS are associated with a variety of poor outcomes including increased disability, poor quality of life and high healthcare costs. The aim of this systematic review is to review the relevant literature to determine the prevalence of MUS in patients who are high users of healthcare and/or who accrue high healthcare costs.Methods and analysis This review will include studies with cases that are either high users of general healthcare or are patients who accrue high healthcare costs, aged ≥18 years and where a recognised measure of MUS, either a standardised clinical interview or questionnaire, was employed. The following citation databases MEDLINE, PsycINFO, EMBASE, CINAHL, PROSPERO and the Cochrane library will be systematically searched from inception to 30 June 2018. The Cochrane library was included because of the significant proportion of non-observational studies currently published in the database. The prevalence of MUS and associated disorders along with the costs or use of healthcare associated with the presence of MUS will be estimated with 95% CI. If possible, study results will be pooled into a meta-analysis. However, if heterogeneity is high, data analysis will be presented descriptively.Ethics and dissemination Ethical approval is not required for this systematic review since only data from existing studies will be used. Results of this review will be disseminated in peer-reviewed publications and at national and international conferences.PROSPERO registration number CRD42018100388